2008
DOI: 10.1080/01612840802182904
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Status of Geriatric Patients in a Psychiatric Hospital

Abstract: Dehydration negatively impacts geriatric hospitalization outcomes. The purpose of this study was to investigate the hydration status of psychogeriatric inpatients and explore possible factors for dehydration. A descriptive, retrospective chart review of patients discharged from a psychogeriatric unit was completed. Clinical and biochemical information was collected at three time points (admission, mid-point, and discharge). Results were consistent with clinical observations that less hydrated patients seem to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Several studies have reported inaccuracies of such charts, especially in residential homes (1,9,10). In one study, onethird of residents whose fluid intake placed them at risk of dehydration were not identified (1).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported inaccuracies of such charts, especially in residential homes (1,9,10). In one study, onethird of residents whose fluid intake placed them at risk of dehydration were not identified (1).…”
Section: Introductionmentioning
confidence: 99%
“…Subjects involved in this secondary analysis consisted of 202 patients aged 65 years or older who were hospitalized in the psychogeriatric unit. Detailed demographic and clinical information of this sample have been published previously (Forsyth et al., ) and are the same as noted earlier.…”
Section: Resultsmentioning
confidence: 99%
“…Our study is a secondary analysis of the primary study dataset from a retrospective review, and it therefore has similar limitations (i.e., a single treatment setting, missing data, and chart review of electronic medical record documentation conducted over time, resulting in older data) (Forsyth et al., ). Our analysis was also not designed for in‐depth examination of other factors that influence LOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially among the elderly population, there is a decreased sensation of thirst that may lead to dehydration [1,2]. Amentia is often caused by dehydration and can be treated by hydration [3]. In the THIRST study, it could be shown that elderly patients presenting with acute ischaemic stroke or transient ischaemic attack had significantly higher plasma osmolarity levels than matched healthy control subjects, suggestive of volume depletion [4].…”
Section: Introductionmentioning
confidence: 98%